Mainstreaming forecast based action into national disaster risk management systems: experience from drought risk management in Kenya. (14th September 2022) - Mwangi, Emmah; Taylor, Olivia; Todd, Martin C.; Visman, Emma; Kniveton, Dom; Kilavi, Mary; Ndegwa, William; Otieno, George; Waruru, Shamton; Mwangi, John; Ambani, Maurine; Abdillahi, Halima; et al.
ABSTRACT: Drought and food security crises heighten risks to lives and livelihoods in East Africa. In recent years, a shift towards acting in advance of such events has gained momentum, notably among the humanitarian and development community. This shift is premised on tools that link climate forecasts with pre-agreed actions and funding, known as Forecast-based Action (FbA), or anticipatory action more widely. While FbA approaches have been developed by a number of humanitarian agencies, the key to scaling-up is mainstreaming these approaches into national risk management systems. This paper addresses this gap in the context of drought risk management in Kenya. We analyse Kenya's current drought management system to assess the potential usability of climate forecast information within the existing system, and outline steps towards improved usability of climate information. Further, we note the critical importance of enabling institutions and reliable financing to ensure that information can be consistently used to trigger early action. We discuss the implications of this for scaling-up FbA into national risk management systems.